THE USE OF RIDDLES GAME TO TEACH SPEAKING TO THE STUDENTS - Episiasi, Episiasi (JURNAL SMART, 2017)
The objective of this study was to find out whether or not it was significantly effective to use Riddles Game to teach speaking at the eleventh grade students. The method applied was pre-experimental method with one group pre-test and post-test design. The sample was 29 students which taken through cluster random sampling. The writer used oral test as technique for collecting the data. The data obtained were analyzed through four techniques : (1) The mean studentsâ score in the pre-test was 56.25, (2) The mean studentsâ score in the post- test was 75.96, (3) The result of normality test in the pre-test was 6.79 and in the post-test was 8.73 and (4) The result of matched t-test was 7.61, which was higher than 1.701 value of the table with the degree of freedom (29-1) 28 with 5% signficant level for one tailed test. So, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that, it was sigificantly effective to use Riddles Game to teach speaking.